A Socio‐Technical Perspective To The Right To The City: Regularizing Electricity Access in Rio de Janeiro's Favelas. (15th June 2017) - Pilo', Francesca
Abstract: This article takes the contemporary transformation in electricity access in Rio de Janeiro's favelas as a starting point for a broader review of the relationship between the right to the city in informal settlements and the neoliberalization of the electricity service (introduction of full cost recovery and 'the user pays' principle). It examines the socio‐technical process through which contractual customer relationships have been established or restored through regularization of the electricity service in two favelas, namely, the installation of meters and networks. I suggest that applying a science and technology study perspective to the right to the city helps explore both the materiality and the spatial dimension of power and politics and, in so doing, provides an insight into some of the forms of mediation that help reshape recognition, urban practices and the favela dwellers' position within such an essential service. Our analysis shows how the means of recognizing these city dwellers 'by the network' are materially and symbolically reshaped by commercial processes. The question then is whether this right to the city, which is being reshaped by commercial processes, will be the source of new inequalities or new politicizations.